2016
DOI: 10.1007/s11524-016-0030-4
|View full text |Cite
|
Sign up to set email alerts
|

Foreclosure and Health in Southern Europe: Results from the Platform for People Affected by Mortgages

Abstract: Housing instability has been shown to be related to poorer health outcomes in various studies, mainly in the USA and UK. Affected individuals are more prone to psychiatric (e.g., major depression, anxiety) and physical disorders (e.g., hypertension). This situation has deteriorated with the onset of the economic crisis. One of the most affected countries is Spain, which has high rates of foreclosure and eviction that continue to rise. In response, a civil movement, The Platform for People Affected by Mortgages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 23 publications
3
24
0
3
Order By: Relevance
“…The housing crisis has been at the centre of the broader crisis in Spanish political economy since 2008 with foreclosures, repossessions and evictions being some of the main ways in which the crisis has hit many Spanish people (Cano Fuentes et al 2013, Barbero 2015, Vásquez-Vera et al 2016. Moreover, Spanish growth preceding the crisis was largely driven by increasing house prices (López andRodríguez 2010, Charnock et al 2014).…”
Section: The Actually Existing Austerity Of Housing In Spainmentioning
confidence: 99%
See 1 more Smart Citation
“…The housing crisis has been at the centre of the broader crisis in Spanish political economy since 2008 with foreclosures, repossessions and evictions being some of the main ways in which the crisis has hit many Spanish people (Cano Fuentes et al 2013, Barbero 2015, Vásquez-Vera et al 2016. Moreover, Spanish growth preceding the crisis was largely driven by increasing house prices (López andRodríguez 2010, Charnock et al 2014).…”
Section: The Actually Existing Austerity Of Housing In Spainmentioning
confidence: 99%
“…The paper focuses on Spanish housing because the anti-eviction housing movement Plataforma de Afectados por la Hipoteca (PAH, Platform for the Mortgage-Affected) has been one of the most sustained and well-known cases of contestation of austerity in Europe throughout the post-2008 period, with scholars across the social sciences exploring different aspects of the PAH and its campaigns (Álvarez de Andrés et al 2015, Flesher Fominaya 2015, Nuijten 2015, Ordóñez et al 2015, de Weerdt and García 2016, Vásquez-Vera et al 2016. It therefore follows Huke et al (2015) to some extent in understanding the political economy by exploring how it is contested and disrupted.…”
Section: Introductionmentioning
confidence: 99%
“…En el análisis de la calidad de vida de personas afectadas por la crisis hipotecaria se observa una clara afectación negativa sobre su salud (Ballester et al, 2015;Vásquez-Vera et al, 2016). Para tratar el tema de la salud, se aboga por crear comunidad y trabajar de manera cooperada apuntando a la importancia del apoyo psicosocial de las personas afectadas (Arredondo y De las Olas, 2013).…”
Section: Calidad De Vidaunclassified
“…Spain has also had high levels of mortgage arrears and evictions since the economic crisis. One study in Catalonia found that 90% of women and 84% of men in mortgage arrears and threatened with eviction had poor mental health compared with rates of 15% and 10% in the general population (30). A Swedish study linking data on 23,000 court imposed rental evictions found that they were four times more likely to complete suicide than the general population (31).…”
Section: Original Articlementioning
confidence: 99%